DIMENSION DETERMINATION AND STRESS ANALYSIS OF PIPING SYSTEM IN WELL PAD 29 DIENG UNIT I GEOTHERMAL PRODUCTION FACILITY - BHAKTI ARIFMAN , ANDY
Geothermal is one of alternative energy that very potensial in Indonesia. Up to 40% of geothermal energy in this world is located in Indonesia. 27357,5 Mwe geothermal energy that can be produced in Indonesia, but the fact that Indonesia just only used 1052 Mwe until 2008. Geothermal energy production can be maximized by built some geothermal facilities. This facilities have also being supported by piping system design that safe from failure. This final project do some analysis of pipeline construction on the well pad 29 Dieng Unit I.This analysis covers hydraulic analysis with HYSYS program, the selection of the pipe diameter, pipe thickness selection based on ASME B31.1 Power Piping, insulation selection, and the stress analysis of piping systems. Stress analysis of piping design based on ASME B31.1 Power Piping and the model is build with AUTOPIPE program. Hydraulic analysis is used to determine the optimum pipe diameter for reaching the minimum criteria on tie in well pad 7 (12 bar and above 178 oC). Selected material for pipe is ASTM A53 Grade B. This selection is based on results of corrosion analysis on the pipe 2-phase, brine, and wet steam at 20 mpy, while for dry steam pipe at 5 mpy. Modeling of piping systems have been modified to have a high stress resistances. Studies show that the system will fail if the well head moves up about or move down above 0.3 m; the operating pressure is increase up to 30 bar; attacked by the earthquake up to 0.55 times the acceleration of earth gravity and because of the wind velocity above 250 km/hour.